2020
DOI: 10.3389/fneur.2020.582994
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Penumbral Tissue and Blood-Brain Barrier Disruption in Acute Stroke Patients Presenting in an Extended Time Window

Abstract: Background: Penumbral brain tissue identified with multimodal imaging can be salvaged with reperfusion in an extended time window. The risk of severe hemorrhagic complications after reperfusion therapy increases with worsening disruption of the blood-brain barrier (BBB). The relationship between penumbral tissue and BBB disruption has not been previously studied.Methods: Stroke patients presenting in an extended time window without a large vessel occlusion who underwent diffusion-perfusion MRI within 24 h of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However, patients exhibiting a cerebral perfusion deficit, such as in acute stroke, require an arrival time correction for DSC-based permeability imaging to control for altered blood flow effects before calculating the permeability signal [103,105]. Both the DCE-PWI and delay-corrected DSC-PWI techniques to assess BBB permeability have successfully been applied successfully to investigate pre-and post-treatment BBB leakage in previous studies, which demonstrated associations between BBB disruption and haemorrhagic transformation, parenchymal haemorrhage, and unfavourable clinical outcomes [102,104,105,107,108] (Fig. 4).…”
Section: Blood-brain Barrier Dysfunction and Post-stroke Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients exhibiting a cerebral perfusion deficit, such as in acute stroke, require an arrival time correction for DSC-based permeability imaging to control for altered blood flow effects before calculating the permeability signal [103,105]. Both the DCE-PWI and delay-corrected DSC-PWI techniques to assess BBB permeability have successfully been applied successfully to investigate pre-and post-treatment BBB leakage in previous studies, which demonstrated associations between BBB disruption and haemorrhagic transformation, parenchymal haemorrhage, and unfavourable clinical outcomes [102,104,105,107,108] (Fig. 4).…”
Section: Blood-brain Barrier Dysfunction and Post-stroke Seizuresmentioning
confidence: 99%
“…4). Furthermore, a high magnitude of BBB disruption correlates with the degree of hypoperfusion and is associated with poor collateral flow [102], whereas a favourable penumbral profile that predicts a favourable clinical outcome is associated with reduced BBB disruption [108]. As the clinical stroke severity influences the PSE risk, this suggests a link between BBB disruption and PSE.…”
Section: Blood-brain Barrier Dysfunction and Post-stroke Seizuresmentioning
confidence: 99%
“…This relationship was also seen in a recent large CT perfusion–based study. 49 Another interesting finding that has come out of both CT 37 and MRI 53 studies is that better collateralization is associated with less BBB disruption. This may explain why ICH rates remained low in studies that used penumbral imaging to select patients in an extended time window.…”
Section: Pretreatment Imaging Biomarkers Of Post-evt Ichmentioning
confidence: 99%
“…The liposomes are expected to start to degrade once they enter areas of the brain with a raised expression of, e.g., matrix metalloproteinases. This approach does not demand the liposomes to be functionalized by conjugation to a targeting antibody, but the targeting approach could allow for more widespread uptake of the liposomes in the surrounding areas of a central pathology, e.g., in ischemic stroke, the penumbra zone, where the BBB often remains intact [ 80 ]. Targeting to the BECs could enhance the liposomal delivery, which might allow, e.g., enhanced pharmacological preconditioning using focused ultrasound and microbubble treatment [ 81 ].…”
Section: Targeting Nanoparticles To the Brain Endothelium In Patholog...mentioning
confidence: 99%